INSTRUCTIONAL MATERIAL: MULTIPLICATION AND DIVISION TEACHING TOY PENHOLDER - AH NKAYASI, Hamide; AH NKAYASI, Yunis (2023)
This invention (product) is a concrete instructional material that helps primary school students learn and especially reinforce forward-backward rhythmic counting and multiplication-division tables, which they have difficulty in learning at mathematics courses, and allows them to play individually or in groups on the subject. The product consists of a penholder and a toy. The product looks like a vertical cylindrical penholder that the toy is attached at and detached from top face. Multiplication and division equations, which are inverse operations, are simultaneously written on penholder. The students multiply the numbers 1-10 with numbers 1- 10 whenever and wherever they want and write their equations on front side of penholder. They simultaneously write the inverse (division) equations on backside of it (e.g. 5 X 3 =15 and 15/3=5 and vice versa is possible. Students play games individually or in groups on product. In game, students randomly select one of 42 different numbers that are product/dividend in equations, and write equation/ equations of the number they selected on penholder and get points. Students monitor their game performance with game tracking-scoring form and this form gives them feedback-correction. In this product, students study, learn and reinforce forward-backward rhythmic counting and multiplication-division tables both as a whole and modularly.